Lecturers' Motivation and Its Correlation with Students' Activity in The Arabic Learning Process - Moh Yusuf Hidayat (Jurnal Alsinatuna, 2020)
This study aims to explore the extent to which lecturers can motivate students in the teaching and learning process and the effect of their motivation on students' activities in the Arabic learning process. Data were obtained from lecturers of four faculties at IAIN Pontianak and were analyzed with the percentage of non-participant observation and the product-moment correlation. The results showed that the lecturers used various methods and helped the students compete with each other in the teaching and learning process. It is also important to notice that the lecturers' motivation didn't have a significant effect on the students' activities in the Arabic learning process.